Implementation of the Partnership for SMKN 1 Cihampelas with the Industrial World (DUDI) to improve the competence of graduates - Ai Asiah; Achmad Sanusi; Hanafiah; Agus Mulyanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research is motivated by the lack of partnerships between SMK with the Business and Industrial World (DUDI) in the implementation of dual system education, so there is a need for research on the management of partnerships between schools and DUDI in order to improve the quality of graduates so that SMK graduates have guaranteed absorption in the job market. The purpose of this study was to obtain an overview of the partnership management of SMK with DUDI to increase the competence of SMK graduates of West Bandung. The specific purpose is to find out the implementation of the partnership between SMK and DUDI. This study uses a qualitative approach with a descriptive method. Data collection techniques through observation, interviews and documentation studies. The theoretical basis for this research is the management of LF Urwick in Hasibuan, M (2017:3), the partnership of Moss (1984:71) and the Competence of Graduates of the Minister of Education and Culture No. 34 of 2018 concerning SNP SMK/MAK. The results of the research are as follows: Before establishing a partnership, SMK Negeri 1 Cihampelas first prepares the human resources (Human Resources) owned by the school. Then the school conducts a needs analysis of the school's relationship activities with the business/industrial world (DU/DI). Organizing a partnership program is the process of determining, grouping, and regulating the various activities needed to achieve the goals of the partnership program, placing people in each activity, providing the necessary tools, determining the authority that is relatively delegated to each individual who will carry out the activities. these activities. Forms of partnership between Vocational Schools with the Business World and the Industrial World to increase the competency of West Bandung Vocational High School graduates through teaching factories in terms of service and maintenance of household appliances such as refrigerators and washing machines. Improving the quality of schools is carried out by having a business center which is managed by students after getting work experience in the industry, so that students have been tested in the field of engineering. The results of the partnership between SMK with the Business World and the Industrial World are graduates of the study program TPTU 65% annually work in companies that are in accordance with their competencies and 15% work not according to their fields, 20% continue their education. The results of the partnerships that have been implemented to improve the competence of graduates can be seen from the increase in the number of alumni who enter college, work, and become entrepreneurs